Post‐transfusion changes in serum hepcidin and iron parameters in preterm infants. Issue 2 (22nd February 2018) - Stripeli, Fotini; Kapetanakis, John; Gourgiotis, Dimitris; Drakatos, Antonis; Tsolia, Maria; Kossiva, Lydia
Abstract: Background: Packed red blood cell transfusion is common in preterm neonates. Hepcidin acts as a negative feedback iron regulator. Iron parameters such as immature reticulocyte fraction (IRF) and high‐light‐scatter reticulocytes (HLR) are used to clarify iron metabolism. Very little is known about the regulation of hepcidin in preterm infants because most reports have evaluated prohepcidin. The aim of this study was therefore to evaluate serum hepcidin and establish hematological parameters in preterm infants after transfusion. Methods: The subjects consisted of 19 newborns (10 boys) with mean gestational age 29.1 ± 2.0 weeks, who had been transfused at the chronological age of 44.84 ± 19.61 days. Blood sample was collected before the transfusion and thereafter at 5 days and at 1 month. Serum hepcidin and other iron parameters were evaluated. Results: Mean serum hepcidin before and 5 days after transfusion was significantly different (5.5 ± 5.1 vs 10 ± 7.9 ng/mL respectively, P = 0.005). IRF and % HLR were also decreased significantly, 5 days after transfusion (0.4 ± 0.2 vs 0.2 ± 0.1, P = 0.009; 1.4 ± 1.5% vs 0.5 ± 0.4%, P = 0.012, respectively). Changes in hepcidin 5 days after transfusion were correlated significantly with changes in mean corpuscular hemoglobin (β, 0.13; SE, 0.05; P = 0.017), total iron binding capacity (β, 3.74; SE, 1.56; P = 0.016) and transferrin (β, 2.9, SE, 1.4; P = 0.039). Conclusions: Serum hepcidin concentration, along with IRF and HLR, are potentially useful in estimating pre‐ and post‐transfusion iron status. Larger studies are needed to evaluate the sensitivity and specificity of hepcidin compared with ordinary iron parameters in premature infants.